A Descriptive-contrastive analysis of English and Pampango consonant and vowel sounds - Mallari, Myrel Q. (College of Arts and Letters, University of the Philippines Diliman, 2002)
Most Kapampangans commit errors in pronouncing English words that start with the sounds /f, v, h/, particularly the grade II pupils of Dolores Elementary School. This study aims to determine the common pronunciation errors of the grade II pupils, the sources of these errors, and the measures that can be adopted by the English language teachers in Dolores Elementary School. Robert Lado's Contrastive Analysis Hypothesis was used in studying and analyzing problem. The Pampango sound system was compared with the English sound system, in order to determine the sounds that are similar with English and those are different. In the analysis, the consonant sounds /p, b, t, d, k, g, m, n,, s, h, t, d3, l, r/, and the vowel sounds /I, ɛ, a/ are not problem in pronunciation for the grade II students because these are present in both in the two languages. The consonant sounds /f, v, z, ø, 3/ and the vowel sounds /i, e, æ, o, u, ð/ are predicted to be pronunciation problems for the grade II pupils because these sounds are absent in the Pampango sound system.